Stability of spatial patterns in a diffusive oxygen-plankton model with time lag effect - Gokce, Aytul; Yazar, Samire; Sekerci, Yadigar (Elsevier, 2022)
Although marine ecosystem is a highly complex phenomenon with many non-linearly interacting species, dissolved oxygen and plankton among these have perhaps the most fundamental relationship not only for the protection of marine environment but also for continuation of life on Earth. This paper deals with a generic diffusive model of dissolved oxygen, phytoplankton and zooplankton species, for which constant time delays are incorporated in growth response of phytoplankton and in the gestation time of zooplankton. We mainly focus on the stability analysis of the coexisting states and the existence of Hopf bifurcation through the characteristic equation, where time delay and oxygen production rate are considered as control parameters for all cases. Studying the effect of both time delays on a stable system, we show destabilisation of the system and irregularity in the spatio-temporal dynamical regimes, leading to chaotic oscillations. Although both delay terms have a destabilising effect, our findings indicate that time delay in zooplankton gestation may induce sharp strongly irregular pattern, whereas time delay in phytoplankton growth gives rise to more regular but higher frequency oscillations for oxygen-plankton interactions. The findings of this paper may provide new insights into main environmental issues including global warming and climate change.(c) 2021 International Association for Mathematics and Computers in Simulation (IMACS). Published by Elsevier B.V. All rights reserved.
Keywords: Time delay; Prey-predator interactions; Oxygen-plankton system; Hopf bifurcation; Chaos; Spatio-temporal pattern formation